Ginsenoside Rb2 alleviates myocardial ischemia/reperfusion injury in rats through SIRT1 activation. Issue 11 (18th October 2020) - Xue, Yan; Fu, Wenwen; Liu, Yanzhe; Yu, Ping; Sun, Mingyang; Li, Xin; Yu, Xiaofeng; Sui, Dayun
Abstract : Abstract: The cardioprotective effects of ginsenoside Rb2 on oxidative stress, which is induced by hydrogen peroxide and myocardial ischemia/reperfusion (MI/R) injury, have been studied. The mechanisms were associated with the inhibition of cardiomyocyte apoptosis, a high concentration of antioxidant defense enzymes, and scavenging oxidative stress products. Because of the association with oxidative reaction and cardioprotection, sirtuin‐1 (SIRT1) was selected as a promising target for investigating whether MI/R injury can be alleviated by ginsenoside Rb2 pretreatment through SIRT1 activation. The rats were exposed to ginsenoside Rb2 with or without SIRT1 inhibitor EX527 before ligation of coronary artery. Ginsenoside Rb2 reduced myocardial superoxide generation; downregulated gp91 phox expression; and decreased the mRNA expression levels and activities of interleukin‐1β, interleukin‐6, and tumor necrosis factor‐α. The results demonstrated that ginsenoside Rb2 significantly attenuated oxidative stress and inflammation induced by MI/R injury. In addition, ginsenoside Rb2 upregulated SIRT1 expression and downregulated Ac‐p53 expression. However, EX527 blocked the protective effects, indicating that the pharmacological action of ginsenoside Rb2 involves SIRT1. Our results thus revealed that ginsenoside Rb2 alleviated MI/R injury in rats by inhibiting oxidative stress and inflammatory response through SIRT1 activation. Practical Application: Ginsenoside Rb2 has a protective effect on MI/R injury by activating SIRT1 expression, reducing myocardium inflammation, and alleviating oxidative stress. Thus, ginsenoside Rb2 is a promising novel agent for ameliorating MI/R injury in ischemic heart diseases and cardiac surgery.